Smart and green buildings features in the decision-making hierarchy of office space tenants: An analytic hierarchy process study - Michal Gluszak; Remigiusz Gawlik; Malgorzata Zieba (Administrative Sciences, 2019)
In the paper, we investigate the role of smart building or green building innovations on the Polish real estate market using the Analytic Hierarchy Process (AHP) method on the group of experts (consultants, managers, brokers) that are active on the office market in Krakow (study area). The findings point towards the highest relevance of the localisation factor, but also at the relatively low importance of the features of a sustainable building: building automation and information technology systems, as well as energy efficiency or certification. The findings suggest that despite the growing interest in sustainability and technological advancement amongst office market participants in Krakow, the relative importance of smart and green building features in their decision-making processes is relatively low. The study has some interesting practical implications. The knowledge regarding the relative importance of decision criteria can be valuable for developers and investors because the anticipation of tenants' expectations is directly linked with return on investment and innovation premiums.
Keywords: 350; sustainable real estate; office market; smart building; green building; Industry 4.0; analytic hierarchy process; MCDM